3434 The Study of Fetal Tracheal Occlusion to Treat Congenital Diaphragmatic Hernia in the EXTEND Model - Coons, Barbara Elizabeth (J Clin Transl Sci, 2019)
OBJECTIVES/SPECIFIC AIMS: The goal of this project is to study fetal pulmonary vasculature in a CDH animal model, to understand how FETO affects developing vasculature, and to develop a modifiable fetal tracheal occlusive therapeutic device that avoids previously seen sequelae of FETO, like alveolar distension, decreased surfactant production, and decreased Type II Pneumocytes. The primary outcome is lung volume/kilogram. The secondary outcomes are contrast-enhanced ultrasound perfusion metrics (Time to Peak, Mean Transit Time, Wash-in Rate, Wash-in Perfusion Index), pulmonary vascular density, Lung Injury Histology Scores, and Lung Compliance upon ventilation. METHODS/STUDY POPULATION: Congenital diaphragmatic hernias will be modeled by surgical hernia creation via maternal laparotomy and hysterotomy at gestational age 72 - 74 days. The ewe will undergo a second laparotomy at 105 - 115 days gestational age. After a second hysterotomy is made, the fetus will be removed from the amniotic sac, though placental circulation will be maintained (EXIT Procedure). The animal is cannulated via the umbilical vein and arteries onto the pumpless ECMO circuit. The balloon and pressure sensor complex is placed into the trachea via direct laryngoscopy, and the fetus aseptically sealed into the Biobag. The wires of the tracheal occlusive device (balloon catheter and pressure sensor) will egress via the port of the Biobag. The fetus remains in the Biobag for fourteen days, with the tracheal occlusive device in place for ten days, followed by a four day recovery period. Daily contrast-enhanced ultrasounds and pulmonary artery dopplers are performed. Upon study completion, the fetus is intubated and placed on a conventional ventilator. A full necropsy is then performed, with perfusion fixation of the lungs via the pulmonary artery. RESULTS/ANTICIPATED RESULTS: Hypothesis 1: Modifiable Tracheal Occlusion will have statistically different effects on developing lung parenchyma, surfactant production, and abundance of Type II Pneumocytes Hypothesis 2: Modifiable Tracheal Occlusion will have lower levels of pulmonary hypertension than negative control animals, as measured by contrast-enhanced ultrasound (pulmonary artery velocity and washout time). DISCUSSION/SIGNIFICANCE OF IMPACT: This project will provide insight into the development of pulmonary hypertension in the CDH fetus. It will provide insight into the physiology of FETO, a novel therapy for congenital diaphragmatic hernias, and will demonstrate the utility of the EXTEND System for fetal treatments that are not possible in the maternal uterus.